UJI KETURUNAN SAUDARA TIRI ( Half - sib ) SENGON ( Paraserianthes falcataria L. Nielsen) DI TAMAN HUTAN BLOK CIKABAYA - Ali Mukmin; Iskandar Zulkarnaen Siregar (Jurnal Manajemen Hutan Tropika, 2007)
Analysis of genetic parameters in seedling seed orchard progeny trial of Paraserianthes falcataria at Taman Hutan Blok Cikabayan are very important to decide to continue  the breeding program.  The analysis was coducted on estimation of individual heritability and genetic correlation between traits. Result of analysis shows that individual heritability for height, diameter and form traits.